Prognostic significance of TLR3 and TLR9 gene polymorphism in assessing the severity of COVID-19 - L. A. Ashchina; N. I. Baranova; A. I. Bolgova; O. A. Levashova; O. N. Lesina (Журнал инфектологии, 2024)
Objective: to study polymorphic variants of TLR3 (rs3775291) and TLR9 (rs352140) genes in patients with COVID-19 depending on the severity of the disease and their significance for determining the risk of severe course of COVID-19.Materials and Methods: genetic analysis of polymorphism of TLR3 (rs3775291) and TLR9 genes (rs352140) was performed in 164 patients with COVID-19, who were divided by degree of severity into three groups: Group 1 with mild, Group 2 with moderate and Group 3 with severe and extremely severe degrees of severity. The control group consisted of 40 healthy donors. Statistical processing of the obtained results was carried out using STATISTICA 12.0 programs (Stat Soft, USA). To assess the difference of groups by qualitative characteristics, the χ2 criterion with Yates correction was used, and in case of violation of its conditions, the χ2 criterion was applied. Yates correction, and if the conditions of its applicability were violated, the two-sided Fisher’s two-sided criterion (RF). The difference between the groups was considered statistically significant at р<0,05. The strength of associations was evaluated in the values of the odds ratio index odds ratio (OR) and 95% confidence interval.> ˂ 0,05. The strength of associations was evaluated in the values of the odds ratio index odds ratio (OR) and 95% confidence interval.Results: the frequency of the ST genotype was significantly higher and the frequency of the TT genotype of the rs3775291 allele of the TLR3 gene was significantly lower in patients with the manifest form of COVID-19 compared with the control group. Frequency analysis of TLR9 (rs352140) in COVID-19 patients showed significantly higher values of the ST genotype and lower values of the CC genotype compared to healthy individuals. Comparative analysis between groups of hospitalized patients depending on severity revealed higher frequency of ST genotype and lower frequency of TT genotype of TLR3 (rs3775291) and TLR9 (rs352140) genes in patients with severe and extremely severe condition.Conclusion: reliable differences in the frequency of occurrence of genotypes of TLR3 (rs3775291) and TLR9 (rs352140) genes in patients with the manifest form of COVID-19 compared to healthy people were revealed. The analysis of nucleotide sequence variants of the studied genes in hospitalized patients depending on the degree of severity also showed significant differences in the frequency of genotypes. Thus, in patients with severe and extremely severe COVID-19, a significant difference in the frequency of occurrence of ST and TT genotypes of TLR3 (rs3775291) and TLR9 (rs352140) genes was revealed compared to patients with mild and moderate COVID-19, which may further have prognostic value in assessing the severity of the disease.